El Demonio de los Andes: Anécdota e Historia - Kapsoli Escudero, Wilfredo (2018)
a narrative resource used by many writers, the anecdote was an essential element in the work of don Ricardo Palma. In fact, the presence of this element managed to enrich and give vitality to that impressive and vast detailed picture of historical events and characters that managed to create the writer of Lima with his pen. It is precisely in El Demonio de los Andes, one of the traditional works of the traditionalist, where history and anecdote complement each other in the best way delighting many readers, but also giving many critics to question the work of Palma as Historian for the recurrent abuse of the anecdote. The present work seeks to delimit the boundaries between history and fiction and the use of the anecdote in the work of the traditionalist.